(untitled) (Mongolian Journal of Humanities and Social Sciences, 2025)
This article aims to clarify the internal ideological connection between the Mongolian Secret History narrative and mythological thinking of the Mongols through a mythological story. With the aim of doing o, we emphasize the agricultural culture of the ancient Mongols and argue that some of the names in the lineage of Chinggis Khaan ancestors are not given names, but carry mythological meanings. The ancient Mongols combined the hunting and agricultural husbandry. The Golden Clan of Chinggis khaan were hunters. The Great State they established was a military empire. Хураангуй: Энэхүү өгүүлэлдээ Монголын нууц товчооны хүүрнэл ба монголчуудын домог зүйн сэтгэлгээний дотоод суртал холбоог нэгэн миф домгийн өгүүлэмжээр тодруулах гэсэн юм. Ингэхдээ өвөг монголчуудын аж ахуйн соёлыг онцолж, Чингис хааны удам дээдсийн цуваан дахь зарим нэр нь оноосон нэр бус, харин домог зүйн утгатай хэмээн үзлээ. Өвөг монголчууд мал аж ахуй, ан гөрөөг хослон эрхэлж ирсэн билээ. Чингисийн Алтан ургийнхан анчин гөрөөчин удамтай. Тэдний байгуулсан Их Төр нь цэрэг дайны гүрэн байв. Түлхүүр үгс: Домог зүйн сэтгэлгээ, миф домог, суртал номлол, өргөмжит нэр, Тэнгэр үзэл.